Surgeon-patient relationship - Anubhav Jannu; Abhishek Jahagirdar (Elsevier, 2021)
Recent years have seen advances in neuroimaging to such an extent that neuroscientists are able to directly study the frequency, location and timing of neuronal activity to an unprecedented degree. The brain serves many important functions from controlling thoughts, memory and speech, movements of limbs, functioning of many organs, response of people to stressful situations and psychology of Surgeon and patient.The transcendence of psychological factors of the Surgeon-patient relationship is given by the fact of its influence on results and quality of surgical care, improvement in compliance, satisfaction and recall of surgeon information, skillful listening and communication for proper diagnosis and treatment planning.There is a modality of psychotherapy in a Surgeon-patient relationship, where the treatment is based on that relationship. The Surgeon and the patient have to work together to improve psychological conditions through the focus on the therapeutic relationship which brings consequences on thoughts, emotions and behaviors.